El debido proceso para la deportación en Costa Rica - Trejos Robert, Sergio (2026)
In light of the judgment of the Inter-American Court of Human Rights handed down in the Vélez Loor v. Panama case, it can be concluded that the Costa Rican legislation on the administrative procedure of deportation is deficient in two specific aspects: the right of every person deprived of liberty to be brought before a judge and the right to have a technical defense and - if necessary - paid by the State.